2017
DOI: 10.1038/s41523-017-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming underlies metastatic potential in an obesity-responsive murine model of metastatic triple negative breast cancer

Abstract: The vast majority of cancer-related deaths are due to metastatic disease, whereby primary tumor cells disseminate and colonize distal sites within the body. Triple negative breast cancer typically displays aberrant Wnt signaling, lacks effective targeted therapies, and compared with other breast cancer subtypes, is more likely to recur and metastasize. We developed a Wnt-driven lung metastasis model of triple negative breast cancer (metM-Wntlung ) through serial passaging of our previously described, nonmetast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
3
38
0
1
Order By: Relevance
“…O’Flanagan et al has demonstrated that obesity enhances the development and metastatic spread of orthotopically transplanted metM-Wnt lung cells, a triple negative breast cancer (TNBC) cell line that metastasizes to the lung (25). Pascual et al also showed that diet-induced obesity increases the metastatic potential of several types of cancer cells, including oral squamous cell carcinoma, melanoma, luminal breast cancer, bladder cancer and small cell lung carcinoma, in a CD36-dependent manner (26).…”
Section: Introductionmentioning
confidence: 99%
“…O’Flanagan et al has demonstrated that obesity enhances the development and metastatic spread of orthotopically transplanted metM-Wnt lung cells, a triple negative breast cancer (TNBC) cell line that metastasizes to the lung (25). Pascual et al also showed that diet-induced obesity increases the metastatic potential of several types of cancer cells, including oral squamous cell carcinoma, melanoma, luminal breast cancer, bladder cancer and small cell lung carcinoma, in a CD36-dependent manner (26).…”
Section: Introductionmentioning
confidence: 99%
“…Most deaths from breast tumor are due to metastatic disease (O'Flanagan et al., 2017 ) and the five-year survival rate for advanced or metastasized breast tumor is only 26%. For many patients, metastasis has already occurred when tumor is detected (Klein, 2009 ; Ullah et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AT-3 cell line was derived from an MMTV-PyMT transgenic mouse mammary tumor 26 , whereas M-Wnt was established from an MMTV-Wnt-1 transgenic mouse mammary tumor 27 .We chose these two tumor cell lines because both are syngeneic with C57BL/6 mice and have been used as models for triple negative breast cancer [28][29][30][31] . Tumor sizes were assessed by caliper measurement over a period of 4-7 weeks, and tumors were weighed upon harvest.…”
Section: Genetic Ablation Of Host Ddr1 Blunts Mammary Tumor Growthmentioning
confidence: 99%